Does Vertical Educational Mismatch Hinder Economic Growth?: Evidence from Indonesia - Dani Rahman Hakim; Euis Nessia Fitri (Economics Development Analysis Journal, 2025)
Most studies have examined the effects of overeducation and undereducation on individual wages; however, only a few scholars have investigated the impact of this vertical educational mismatch on economic growth. Therefore, this study attempts to enter this area of analysis. The effect of overeducation and undereducation on economic growth was examined using panel data from 33 provinces in Indonesia between 2012 and 2022. Using the System Generalized Method of Moments (Sys-GMM) estimator, this study found empirical evidence that overeducation reduces economic growth. This implies that even if overeducation yields a positive return on individual wages, it remains detrimental at an aggregate level. The negative effect of overeducation on economic growth suggests that overeducation is a form of human capital and external education inefficiency. Thus, it needs to be addressed seriously by the Indonesian government. On the other hand, this study found no evidence that undereducation has an impact on Indonesia's economic growth.